COMPARISON OF OUTCOME WITH OR WITHOUT ASPIRIN IN PATIENTS UNDERGOING CORONARY ARTERY BYPASS SURGERY - IQBAL, H; KHALID, W; INAM, T; AAMIR, M (Biological and Clinical Sciences Research Journal, 2022)
Preoperative use of aspirin in coronary artery bypass graft surgery (CABG) might rely more on surgeon’s preference rather than on evidence-based approach. Conflicting guidelines and lack of reliable recommendations make ambiguous the preoperative aspirin administration before elective CABG. This study was conducted to compare the outcome with or without aspirin in patients undergoing coronary artery bypass surgery. The aim of the study was to compare the outcome with or without aspirin in patients undergoing coronary artery bypass surgery. This Randomized controlled trial was conducted at the Department of Cardiac Surgery, AFIC/ NIHD, Rawalpindi from 11th Dec 2018 to 10th June 2019. One hundred and fifty patients fulfilling inclusion criteria underwent through CABG were divided into two groups. In group A, 75 patients continued aspirin, while in group B, aspirin was stopped 5 days before surgery. Patient’s demographic features, comorbid conditions, Postoperative bleeding, perioperative MI and need for blood transfusion were noted. The mean age and BMI of patients were 61.41 ± 3.09 and 63.96 ± 7.64 years and 28.98 ± 2.46 and 32.61 ± 1.98 Kg/m2 in group A and B, respectively. Male to female ratios were 3.41:1 and 4.35:1 in group A and B, respectively. Diabetes and hypertension were seen in 67(89.34%) and 59(78.67%) patients and 69(90.67%) and 70(93.34%) patients in group A and B, respectively. Perioperative MI and blood transfusion were statistically significant among both groups (5.34% vs. 9.34% patients; p=0.0001 and 5.34% vs. 1.34%; p=0.0003). Mean postoperative bleeding was 401.39 ± 121.04 and 389.21 ± 101.13 ml/24 hr. in group A and B, respectively. The continuation of aspirin therapy in patients undergoing elective CABG reduces perioperative MI, increases quantity of postoperative bleeding and need for blood transfusion. There is a significant difference in outcome with or without aspirin in patients undergoing coronary artery bypass surgery.